MAKING NATUREâ€™S VALUE VISIBLE: VIDEO ARTISTS AS CITIZEN SCIENTISTS - Van Borek, Sarah (European Scientific Journal, ESJ, 2014)
Rewilding vancouver community projects was a community mapping, storytelling & visioning project designed to reconnect residents in the Metro Vancouver region of British Columbia, Canada with the cityâ€™s â€œwild sideâ€ (the historical natural environment) and to help â€œmake visibleâ€ the different forms that nature takes in Vancouver as ways to inspire the valuing, protection and potential â€œrewildingâ€ of nature.. The project was developed through a two-semester cross-disciplinary studio-based community projects course in the Faculty of Culture + Community at one of Canadaâ€™s leading post-secondary art institutions, the Emily Carr University of Art + Design (Vancouver), in partnership with one of Canada’s leading environmental organizations, the David Suzuki Foundation (DSF), and the bold, contemporary Museum of Vancouver (MOV). Postsecondary art students across a variety of levels and disciplines were facilitated in producing a media arts-based â€œvirtual urban safariâ€ as part of the MOVâ€™s Rewilding Vancouver exhibit running February 27-September 1, 2014. This exhibit is believed to be the first of its kind in Canada to feature the historical ecology of a major city. Many of the students, by their own self-description, came into the course feeling disconnected from the natural world themselves. The course was structured in a way that encouraged students to reconnect with nature in the city through their creative process. The course culminated in a public screening and dialogue, offering the students the opportunity to see the effects of their work on a public audience and feel like their input could have an impact.